Development and Validation of a Stability-Indicating Reversed-Phase HPLC Method for Assay and Estimation of Related Substances of Ivermectin in an Oral Paste. (21st January 2022) - Padivitage, Nilusha; Tian, Jingzhi; Wang, Lin; Zhuang, Jinyou; McAdoo, Andrew; Zhao, Daoli; Rustum, Abu M
Abstract: Ivermectin is a potent semi-synthetic antiparasitic drug used in veterinary medicine. A reversed-phase high performance liquid chromatography (HPLC) method has been developed and validated for the identification and assay of Ivermectin, including the identification and estimation of its related impurities in an oral paste. Analytes were separated using a gradient elution at a flow rate of 1.5 mL/min on a Zorbax Extend-C18 column (150 mm × 4.6 mm i.d., 3.5-μm particle size) maintained at 30 °C. The mobile phase was composed of water as mobile-phase A and acetonitrile/methanol (85/15, v/v) as mobile-phase B. Ultraviolet detection at 245 nm was employed to monitor the analytes. Limit of quantitation (LOQ) and limit of detection (LOD) of the method are 0.6 and 0.2 μg/mL, respectively. The validation results demonstrated excellent linearity of the method in the range of 0.1–150% of the analytical concentration (0.6 mg/mL) of the method. The stability-indicating capability of the method has been demonstrated by adequately separating the degradation products from the stress degraded samples of the oral paste as per method validation requirements prescribed in the current International Council for Harmonisation guidelines.